Peningkatan Hasil Belajar IPS Menggunakan Model Cooperative Learning Tipe STAD di Kelas IV SD - Utriana, Atika; Arwin, Arwin; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was improve the students achievement in learning social science used STAD of 4th grade elementary school. Types of this research was classroom action research with qualitative and quantitative approach. Subject of this research were students of 4th grade were 24 people consist of 10 men and 14 women. Research conducted in two cycles with research procedure includes of planning, implementation, observation, and reflection. The result of research was improve a) Lesson plan the cycles of I was 82,14% and the cycles II of 92,85% b) Implementation teacher’s activity of I cycle was 79,68%  and II cycle was 93,75% while implementation students activity of I cycle was 76,56% and II cycle was 90,62% c) the students learning outcomes in the I cycle was 77,21 and II cycle was 87,28. It can be concluded that used STAD model can improve students achievement in learning social science of 4th grade at SDN 18 Padang.Keyword : Learning outcomes; Social science; STAD